High School to University in Ontario: How Effective is the New Grade 12 Curriculum? - Brady, Patrick; Allingham, Philip (Alberta Journal of Educational Research, 2007)
The dual Ontario graduating class of 2003, commonly referred to as the Double Cohort, was the product of that provincial government’s initiative to eliminate the long entrenched practice of requiring a fifth year of secondary school for university-bound students. The new, more “rigorous” four-year curriculum, the Ministry of Education asserted, would be as effective as the previous Ontario Academic Credit (OAC) system in preparing graduating students for further education at the postsecondary level. This study, conducted in a small Ontario university, examines the efficacy of the new curriculum by comparing how effectively the two subgroups, the former grade 12s and the former OAC graduates, had made the transition to postsecondary education both socially and academically. The results suggest that the recently adopted four-year secondary school program has been successful in that there was no significant difference between the two groups in terms of academic achievement or social adjustment.